Deoxygenation Of Palmitic Acid To Diesel-Like Hydrocarbons Via NI-SBA-15 - Saadon, Nur Aziah (Universiti Sains Malaysia, 2017)
The solventless deoxygenation of palmitic acid to diesel-like hydrocarbons using nickel functionalized SBA-15 catalyst was investigated. Various nickel functionalized SBA-15 catalyst were synthesized by varying the nickel loading from 5 to 10 wt% at the same preparation conditions. The nickel functionalized SBa-15 catalysts were characterized in terms of its morphology and chemical compositions by means of scanning electron microscope (SEM) and energy dispersive X-ray (EDX) respectively. Activity test was performed on the nickel functionalized SBA-15 catalysts for solventless deoxygenation reaction of palmitic acid in a semi batch reactor and was confirmed as a promising catalyst. In the study on the effects of the operating conditions on the deoxygenation reaction via nickel functionalized SBA-15 catalysts, it was found that palmitic acid conversion increased with increasing temperature, reaction time and catalyst loading. Furthermore, yield of 1-pentadecene and npentadecane increased with increasing reaction time and catalyst loading. However, the selectivities of both desired products decreased with increasing temperature, reaction time and catalyst loading. The yield and selectivity of n-pentadecane is higher than 1-pentadecene regardless of the operating conditions.